The black book on Turin's pre-removal detention center (CPR). When legal turns political - Veglio, Maurizio (Frontiers in Human Dynamics, 2023)
The paper describes how NGOs, lawyers’ associations and civil society reacted to the suicide of a young man from Guinea while detained in Turin’s Pre-Removal Detention Centre (CPR), where migrants are detained for the sole purpose of deportation. Deprivation of freedom without any criminal record entails a legal scandal, something that challenges the rule of law: the limitation of freedom is reserved to non-EU citizens who now come under the jurisdiction of lay judges (Justice of the Peace), despite decisions on personal freedom are exclusively handled by full professional judges. Furthermore, the legal ground for the detention of undocumented migrants is surprisingly fragile and fragmentary, often resorting to mere ministerial circulars where a law should be mandatory. Defying almost 25 years of indifference, silent acceptance and ignorance, the network of activists launched a campaign to shut the CPR down, publishing the Black Book on Turin’s CPR and raising the public attention against the segregation of migrants through individual accounts and lived experiences.